Given beta distribution as: $$ \mathcal{B}(x;a,b) = \frac{\Gamma(a+b)}{\Gamma(a)\Gamma(b)} x^{a-1} (1-x)^{b-1} $$

I am trying to show: $$ \int_0^1 x^{a-1} (1-x)^{b-1}\,dx = \frac{\Gamma(a)\Gamma(b)}{\Gamma(a+b)} $$

which can be considered as the normalizing constant.

Here is what I have done so far (using the hints at Bishop's). Write $\Gamma(a)\Gamma(b)$ and change variable $t=y+x$ fixing $x$:

\begin{align*} \newcommand{\ints}{\int_0^\infty\!\!\int_0^\infty} \Gamma(a)\Gamma(b) &= \int_0^\infty \exp(-x)x^{a-1} \, dx \int_0^\infty \exp(-y)y^{b-1} \, dy \\ &= \ints \exp(-x)x^{a-1} \exp(-y)y^{b-1} \, dx\,dy \\ &= \ints e^{-t} x^{a-1}(t-x)^{b-1} \, dt\,dx \end{align*}

Now if we make the variable change $x=\mu t$ \begin{align*} \ints e^{-t} x^{a-1}(t-x)^{b-1} \, dt\,dx &= \ints e^{-t} (\mu t)^{a-1} (t-\mu t)^{b-1} t \, dt\, d\mu \\ &= \ints e^{-t} t^{a+b-1} \mu^{a-1} (1-\mu)^{b-1} \, d\mu \, dt \end{align*}

We can split the integrals: \begin{align*} &= \underbrace{\int_0^\infty e^{-t} t^{a+b-1} \,dt}_{\Gamma(a+b)} \underbrace{\int_0^\infty \mu^{a-1} (1-\mu)^{b-1} \, d\mu}_{\text{limits are not from 0 to 1}} \end{align*}

What is wrong with the limits? Is it my mistake? Or can it be substituted to from $0$ to $1$?

PS. sorry for the big space between double integrals, I don't know the right way to do them.


The problem is in the last step here:

$$ \begin{align*} \newcommand{\ints}{\int_0^\infty\int_0^\infty} \Gamma(a)\Gamma(b) &= \int_0^\infty \exp(-x)x^{a-1} \, dx \int_0^\infty \exp(-y)y^{b-1} \, dy \\ &= \ints \exp(-x)x^{a-1} \exp(-y)y^{b-1} \, dx\,dy \\ &= \ints e^{-t} x^{a-1}(t-x)^{b-1} \, dt\,dx \end{align*} $$

As you made change of variables $t=x+y$, naturally $t \geqslant x$, thus the last integral should be $$ \int_0^\infty \exp(-t)\left( \int_0^t x^{a-1} (t-x)^{b-1} \mathrm{d}x\right) \mathrm{d}t \stackrel{x=\mu t}{=} \int_0^\infty \exp(-t) \left( t^{a+b-1} \int_0^t \mu^{a-1} (1-\mu)^{b-1} \mathrm{d}\mu\right) \mathrm{d}t = \\ \int_0^\infty t^{a+b-1}\mathrm{e}^{-t} \mathrm{d}t \cdot \int_0^1 \mu^{a-1} (1-\mu)^{b-1} \mathrm{d} \mu $$

  • $\begingroup$ Thank you for the answer. Can you explain the limit change from (0,t) to (0,1) a little bit in detail? It has been years since I have taken the calculus course :) A link is fine too. $\endgroup$ – nimcap Dec 5 '12 at 20:33
  • 1
    $\begingroup$ With $x = \mu t$, $\mathrm{d} x = t \mathrm{d} \mu$, integration interval $ 0 < x < t$ translates into $0 < \mu t < t$ impliying $0<\mu<1$ for $t>0$. Thus, for $t>0$: $$\int_0^t x^{a-1} (t-x)^{b-1} \mathrm{d}x = \int_0^1 (\mu t)^{a-1} (t - \mu t)^{b-1} t \mathrm{d} \mu = t^{a+b-1} \int_0^1 \mu^{a-1} (1-\mu)^{b-1} \mathrm{d} \mu $$ $\endgroup$ – Sasha Dec 5 '12 at 21:39

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.